(untitled) (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract : Government policies to improve the livelihood of the community improvement in poverty reduction to date continues to be carried out, even a variety of programs have been proposed by the Government to reduce the gap between the rich and the poor. In connection with the program, the Government of Indonesia mencenangkan National Community Empowerment Program Self-sustaining Rural with inside are program development and infrastructure programs and Save Loan women who become the focus in this research. Aiming to find out the impact of the policy of National Community Empowerment Program Selfsufficient Rural Community Livelihood improvement in the village of Paslaten sub-district of Remboken. The researchers used a qualitative method, infoman in this study amounted to 9 people. Instruments and data collection Techniques are in use are guidelines for interviews and help with interviews and observation. Keyword: impact pnpm, standard of living